2018
DOI: 10.1038/s41598-018-25013-7
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Terahertz Photoconductive Antenna Performance with Optimised Plasmonic Nanostructures

Abstract: Advanced nanophotonics penetrates into other areas of science and technology, ranging from applied physics to biology, which results in many fascinating cross-disciplinary applications. It has been recently demonstrated that suitably engineered light-matter interactions at the nanoscale can overcome the limitations of today’s terahertz (THz) photoconductive antennas, making them one step closer to many practical implications. Here, we push forward this concept by comprehensive numerical optimization and experi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 53 publications
0
47
0
2
Order By: Relevance
“…This enhancement occurs due to surface plasmon waves 44 so that the field enhancement near the electrodes becomes much greater than the electric field of the incident wave. 45,46 The idea to use plasmonic metasurface to manipulate the optical wave and to increase the efficiency of PCA started with the discovery of extraordinary optical transmission through subwavelength nanostructured arrays. 47 The authors found the unusual optical properties that are related to the coupling of an optical light with plasmons (or electronic excitations) on the surface of the periodically patterned metallic film.…”
Section: Metallic Metasurfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…This enhancement occurs due to surface plasmon waves 44 so that the field enhancement near the electrodes becomes much greater than the electric field of the incident wave. 45,46 The idea to use plasmonic metasurface to manipulate the optical wave and to increase the efficiency of PCA started with the discovery of extraordinary optical transmission through subwavelength nanostructured arrays. 47 The authors found the unusual optical properties that are related to the coupling of an optical light with plasmons (or electronic excitations) on the surface of the periodically patterned metallic film.…”
Section: Metallic Metasurfacesmentioning
confidence: 99%
“…Later, this idea was evolved in Ref. 45, where Lepeshov et al found the optimized size of the Ag nanoislands via numerical simulations. Typical SEM images of the PCA with Ag nanoislands are depicted in Fig.…”
Section: Metallic Metasurfacesmentioning
confidence: 99%
“…Это позволяет получить измеримый оптический отклик даже от крайне малого количества исследуемого вещества, обладающего относительно слабыми оптическими переходами. Примерами применения локализованного плазмонного резонанса могут служить эффекты гигантского комбинационного рассеяния света (SERS) [1], усиленной металлом флуоресценции (MEF) [2], поверхностно усиленного поглощения в ближней инфракрасной области (SENIRA) [3] и другие [4]. Разнообразие применений плазмонных эффектов обусловлено возможностью изменения положения плазмонного резонанса в соответствии с поставленной задачей в широком диапазоне оптических частот путем выбора материала частицы, ее размера, формы и диэлектрического окружения.…”
Section: Introductionunclassified
“…Using this approach and an LT-GaAs substrate with a 5 μm gap size, THz pulses with a peak field of 36 kV cm −1 were generated with an efficiency of 2×10 −3 [37]. Plasmonic gratings and nanoantennas are another approach that have been tested [38][39][40]. These specific structures increase light absorption and reduces the average photo-carrier transport path, allowing the collection of a larger number of carriers on a sub-picosecond time scale, thus increasing quantum efficiency.…”
Section: Introductionmentioning
confidence: 99%